2020
DOI: 10.1177/0706743720915420
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Mood Disorders and Comorbid Addictions: A Systematic Review and Meta-Analysis: Traitement Pharmacologique des Troubles de L’humeur et des Dépendances Comorbides: Une Revue Systématique et une Méta-Analyse

Abstract: Objective: Addiction comorbidity is an important clinical challenge in mood disorders, but the best way of pharmacologically treating people with mood disorders and addictions remains unclear. The aim of this study was to assess the efficacy of pharmacological treatments for mood and addiction symptoms in people with mood disorders and addiction comorbidity. Methods: A systematic search of placebo-controlled randomized controlled trials investigating the effects of pharmacological treatments in people with bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
14

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 67 publications
0
33
0
14
Order By: Relevance
“…Although not specifically indicated for suicidal ideation or behavior, SSRIs have been used with some success in decreasing suicidal ideation alongside other depressive symptoms, and reducing alcohol misuse in depressed alcohol users [ 101 , 117 – 119 ]. SSRIs consistently produce a modest 15–20% reduction in alcohol consumption [ 120 ], however intra-individual reductions in alcohol intake range widely from 10 to 70% [ 120 ].…”
Section: Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not specifically indicated for suicidal ideation or behavior, SSRIs have been used with some success in decreasing suicidal ideation alongside other depressive symptoms, and reducing alcohol misuse in depressed alcohol users [ 101 , 117 – 119 ]. SSRIs consistently produce a modest 15–20% reduction in alcohol consumption [ 120 ], however intra-individual reductions in alcohol intake range widely from 10 to 70% [ 120 ].…”
Section: Alcoholmentioning
confidence: 99%
“…Double-blinded, randomized, placebo-controlled trials for co-occurring MDD/dysthymia and AUD indicate that antidepressants—particularly non-SSRIs—outperform placebo in the treatment of depression [ 122 ], while SSRIs only demonstrate efficacy when restricted to participants without AUD [ 124 ]. Additional meta-analytic research similarly suggests lower performance of SSRIs relative to tricyclics in comorbid MDD and AUD/SUD [ 119 , 125 ], but results should be interpreted cautiously given the potentially mediating roles of study design and sample selection. Additionally, findings regarding depressive symptom reduction are equivocal when controlling for study quality and bias [ 126 ], and antidepressants may not be justified for treatment of alcohol misuse in the absence of MDD [ 118 , 127 ].…”
Section: Alcoholmentioning
confidence: 99%
“…Two studies evaluated pharmacological interventions as a whole. A review of pharmacological treatments for people with concurrent bipolar disorder or depression found no effect on alcohol consumption (SMD − 0.10, 95% CI − 0.24 to 0.04) but did nd an improvement in abstinence (OR 1.46, 95% CI 1.02 to 2.11) [94], unlike a network meta-analysis of pharmacotherapy for AUD which found no improvement in abstinence rate (OR 0.68, 95% CI 0.4 to 1.16, after treatment) [102]. Due to the variation in e cacy across different types of pharmacological intervention, any analysis of pharmacological interventions is likely to be very dependent on the speci c interventions included.…”
Section: Screening Brief Intervention and Referral To Treatment (Sbir...mentioning
confidence: 99%
“…For topiramate, one low quality network meta-analysis found a signi cant increase in continuous abstinence at 84-365 days (OR 1.88, 95% CI 1.06 to 3.34) [98] and a high quality network meta-analysis found a signi cant reduction in total consumption at 3-52 weeks (SMD − 0.77, 95% CI -1.12 to -0.42; NMD − 0.79, 95% CI -1.21 to -0.36), as well as for drinking days and heavy drinking days, but drinks per drinking day and mortality outcomes were not signi cant, and the study noted very low quality of RCTs alongside presence of publication bias[87]. Certainty in the evidence for anticonvulsants was downgraded to very low, due to high risk of bias, high heterogeneity in RCTs, low precision, and presence of publication bias.Four studies evaluated antidepressants for AUD, of which three considered individuals with comorbid depression [68,74,94]. No signi cant effect was observed on alcohol abstinence among people with comorbid major depressive disorder for nefazodone compared with placebo (OR 2.18, 95% CI 0.68 to 7.07)[94]; AUD remission rate compared to control among individuals with comorbid depression for mirtazapine (SMD − 0.78, 95% CI -1.69 to 0.13)[74], SARI (OR 1.85, 95% CI 0.62 to 5.66)[74], tricyclic antidepressants (OR 1.65, 95% CI 0.57 to 4.73)[74]; or continuous abstinence when compared with placebo at 84-365 days for citalopram or escitalopram (OR 1.03, 95% CI 0.33 to 3.16), nefazodone (OR 0.57, 95% CI 0.19 to 1.76), tianeptine (OR 1.22, 95% CI 0.58 to 2.57), or tiapride (OR 0.56, 95% CI 0.3 to 1.05)[98].…”
mentioning
confidence: 99%
“…Although randomized controlled trials and meta-analyses have shown efficacy for antidepressants in MDD with comorbid AUD [ 7 , 8 ], the effects are modest, with a mix of positive and negative studies [ 8 ], with a recent Cochrane review showing no effect when excluding studies with a high risk of bias [ 7 ]. Similarly, studies for treatments to reduce alcohol use in MDD + AUD remain very limited and without clear effect [ 9 ]. Approved AUD medications, such as naltrexone, have been studied in combination with antidepressants with mixed results [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%